Changing epidemiology of hepatocellular carcinoma in Asia - Zhang, Chen‐hao; Cheng, Yifei; Zhang, Shu; Fan, Jia; Gao, Qiang (Liver international, 2022)
Liver cancer is the fifth most common cancer and the second leading cause of malignant death in Asia, and Asia reports 72.5% of the world's cases in 2020. As the most common histological type, hepatocellular carcinoma (HCC) accounts for the majority of incidence and mortality of liver cancer cases. This review presents the changing epidemiology of HCC in Asian countries in recent years. Globally, aged, male and Asian populations remain the group with the highest risk of HCC. Hepatitis B virus (HBV) and hepatitis C virus (HCV) are still the leading risk factors of HCC with a slight decline in most Asian countries, which is mainly attributed to HBV vaccination of newborns, prevention of HCV horizontal transmission and treatment of chronic hepatitis. However, the prevalence of HCC caused by metabolic factors, including metabolic syndrome, obesity and non‐alcoholic fatty liver diseases, is increasing rapidly in Asian countries, which may eventually become the major cause of HCC. Excessive alcohol consumption continues to be an important risk factor as the average consumption of alcohol is still growing. Hopefully, great effort has been made to better prevention and treatment of HCC in most Asian regions, which significantly prolongs the survival of HCC patients. Asian countries tend to use more aggressive intervention than European and American countries, but it remains unclear whether this preference is related to a better prognosis. In conclusion, HCC remains a major disease burden in Asia, and the management of HCC should be adjusted dynamically based on the changing epidemiology.